New Record of Ptilophyllum and related leaf fossils from Kimmeridgian sediments of the Kachchh Basin, western India - Pandey, Dhirendra Kumar; Prakash, Neeru; Fürsich, Franz; Alberti, Matthias; Shekhawat, Rajesh Singh; Das, Neelam; Bhosale, Suraj; Chaskar, Ketan; Page, Kevin N. (Journal of the Palaeontological Society of India, 2021)
Several well-preserved impressions of Ptilophyllum and Cladophlebis from the Upper Kimmeridgian part of the Jhuran Formation at the Jhuran River are described and illustrated. The presence of well-preserved leaf fossils and plant debris suggest an increasing terrestrial influence during the filling of the Kachchh Basin in the Late Jurassic. A lone ammonite collected from a bed below the plant fossil-bearing horizon and identified as Metagravesia cf. decipiens Spath suggests a Late Kimmeridgian age. The cyclically alternating fine-grained, bioturbated, often ferruginous sandstone, and medium- to coarse grained, trough cross-bedded sandstone, suggests shallowing-deepening cycles of a delta lobe with environments ranging from the lower to the upper delta front.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Kachchh; Kimmeridgian; Ptilophyllum; shallowing-deepening cycles